Influence of Doxycycline and InGaAlP Diode Laser at 660 nm Wavelength in the Treatment of Periodontitis Induced in Rats: In Vivo Study - Silveira, Glauco Rodrigues Carmo; de Lima, Daniela Coelho; Cintra, Luciano Tavares Angelo [UNESP]; Brigagão, Maísa Ribeiro Pereira Lima; Ervolino, Edilson [UNESP]; Fernandes, Leandro Araújo (Wiley, 2021)
This study evaluated the influence of Doxycycline (DOX) and Low-Intensity Laser (LIL) (InGaAlP diode laser) as scaling and root planing (SRP) adjuvants in the treatment of periodontitis induced in rats. The rats received periodontal disease induction, and after 7 days, the ligature was removed, and the animals were divided into groups/treatments: NT—receive no treatment; SRP—submitted only to SRP; DOX—submitted to SRP and DOX irrigation; LIL—submitted to SRP and LIL irradiation; and DOX + LIL—submitted to SRP treatments, DOX irrigation and LIL irradiation. The animals were sacrificed at 7, 15 and 30 days, and then, the analyses were performed. A lower concentration of Alpha-glycoprotein acid and Complement 3 was observed in the DOX + LIL group compared to all the other groups in all the periods, and for Complement 4 at 15 and 30 days (P < 0.01). A lower bone loss (BL) was observed in the DOX + LIL group compared to all the other groups in all the periods (P < 0.01). It can be concluded that LIL was effective in the reduction of proteins, and its association with DOX was effective in the reduction of proteins and BL, in the treatment of periodontal induction in rats.